2023
DOI: 10.1017/s136672892200092x
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual toddlers show increased attention capture by static faces compared to monolinguals

Abstract: Bilingual infants rely differently than monolinguals on facial information, such as lip patterns, to differentiate their native languages. This may explain, at least in part, why young monolinguals and bilinguals show differences in social attention. For example, in the first year, bilinguals attend faster and more often to static faces over non-faces than do monolinguals (Mercure et al., 2018). However, the developmental trajectories of these differences are unknown. In this pre-registered study, data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In combination, the evidence converges on the suggestion that bilingually exposed infants demonstrate fundamentally distinct patterns of attentional allocation compared with monolingually exposed infants, disengaging more readily from familiar stimuli and orienting preferentially to novel stimuli. An even more recent investigation suggests that bilingually exposed infants may engage more rapidly specifically to socially relevant stimuli (Mousley et al, 2023). The study also demonstrated increased attentional switching between paired stimuli.…”
Section: Adaptations To Bilingual Experiencementioning
confidence: 99%
“…In combination, the evidence converges on the suggestion that bilingually exposed infants demonstrate fundamentally distinct patterns of attentional allocation compared with monolingually exposed infants, disengaging more readily from familiar stimuli and orienting preferentially to novel stimuli. An even more recent investigation suggests that bilingually exposed infants may engage more rapidly specifically to socially relevant stimuli (Mousley et al, 2023). The study also demonstrated increased attentional switching between paired stimuli.…”
Section: Adaptations To Bilingual Experiencementioning
confidence: 99%
“…Bilingual adults use gestures more often than monolingual adults (Pika et al, 2006), and bilingual children are more likely to incorporate additional information about a target object into their iconic gestures than monolingual children (Wermelinger et al, 2020). Likewise, bilingual toddlers exhibit a heightened sensitivity towards nonverbal communicative behaviour such as pointing gestures, glances, or facial information such as lip patterns (Brojde et al, 2012;Groba et al, 2018;Mousley et al, 2023), and paralinguistic behaviour such as tone of voice (Yow & Markman, 2011a). Furthermore, when monolingual 3-year-olds were exposed to a bilingual-like experience via instructions in their native language (English) mixed with a foreign language (Japanese), they interpreted nonverbal means more like bilinguals (Yow & Markman, 2016).…”
Section: Bilinguals' Communicative Repertoire and Flexibilitymentioning
confidence: 99%